PERANCANGAN PELAPORAN PASIEN RAWAT JALAN MENGUNAKAN APLIKASI DATABASE BERBASIS VISUAL BASIC FOR APPLICATION (VBA) MICROSOFT EXCEL DI RUMAH SAKIT - Mardiawati, Dewi; Dewi, Siti Handam; Zailinda, Meuthia Arini (Ensiklopedia of Journal, 2024)
Internal reports are reports that are used and utilized by the hospital. Based on the initial survey that the researchers conducted, it was found that there were delays in collecting outpatient internal reports and processing was still done manually. The purpose of this study was to determine the design of an outpatient patient reporting database application based on Microsoft Excel's Visual Basic For Application (VBA) in Mental Hospitals Prof Hb Saanin Padang. The method used is Research and Development. The results of the study found that the flow was in accordance with the flow of medical record documents. The basic patient data components used are 20 basic patient data components and 7 outpatient internal report components. The person in charge of recording and reporting outpatient care is 1 officer. The database application design uses UML visual modeling with the types of use case diagrams, class diagrams, and activity diagrams and the programming language is VBA Excel. The use of database applications has been effective and speeds up report processing with usage results of 03.60 minutes. So it can be concluded that the database application design has been effective and in accordance with the needs of the hospital.